2019
DOI: 10.1242/dev.177527
|View full text |Cite
|
Sign up to set email alerts
|

Wheat AGAMOUS LIKE 6 transcription factors function in stamen development by regulating the expression of Ta APETALA3

Abstract: Previous studies have revealed the functions of rice and maize AGAMOUS LIKE 6 (AGL6) genes OsMADS6 and ZAG3, respectively, in floral development; however, the functions of three wheat (Triticum aestivum) AGL6 genes are still unclear. Here, we report the main functions of wheat AGL6 homoeologous genes in stamen development. In RNAi plants, stamens showed abnormality in number and morphology, and a tendency to transform into carpels. Consistently, the expression of the B-class gene TaAPETALA3 (AP3) and the auxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 55 publications
3
23
0
Order By: Relevance
“…While the tissue expression specificity between branch meristems and inflorescence meristems was not established in these experiments, the dynamic gene expression profile in inflorescence and developing floral tissues support its role in Tripidium floral determinism [ 55 , 83 , 84 ]. In wheat, the TaAGL6 acts on staminate floral development by working on TaAPETALA3 [ 85 ]. In Tripidium , the homeotic activity of staminate floral development could be identified by the dramatic increase in transcript abundance of floral homeotic protein AG -like in samples at 80 cm of growth.…”
Section: Discussionmentioning
confidence: 99%
“…While the tissue expression specificity between branch meristems and inflorescence meristems was not established in these experiments, the dynamic gene expression profile in inflorescence and developing floral tissues support its role in Tripidium floral determinism [ 55 , 83 , 84 ]. In wheat, the TaAGL6 acts on staminate floral development by working on TaAPETALA3 [ 85 ]. In Tripidium , the homeotic activity of staminate floral development could be identified by the dramatic increase in transcript abundance of floral homeotic protein AG -like in samples at 80 cm of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors play an important role in regulating the development of plants. Some previous studies have reported that MADS-box [9,14,16,17,26,27,28] and DROOPING LEAF gene of YABBY family [6,15,16] associated with the development of wheat pistillody-stamen. We identify MADS-box and YABBY transcription factors from wheat flower substructure tissues (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of any of the key genes will lead to male sterility. Some reports have demonstrated that mutations of the genes critical for anther and pollen development will result in male sterility [30,31,[34][35][36][37][38]67]. In this study, the metabolic pathways related to male sterility, such as phenylalanine metabolism (ko00360), phenylpropanoid biosynthesis (ko00940), and glutathione metabolism (ko00480), were identified via K-means analysis.…”
Section: Complex Network Regulating Anther Development Of Nwms1mentioning
confidence: 97%
“…Wheat AGL6 transcription factors interact with TaAP3, TaAGAMOUS, and TaMADS13. TaAGL6 plays an essential role in stamen development through transcriptional regulation of TaAP3 and other related genes [38]. These researches have enriched the mechanism study of wheat male sterility.Although plant male development mechanisms are similar, because of the diverse floral phenotypes of various species, the molecular mechanism of wheat male fertility is unique and complicated, and there are many issues that need to be elucidated.…”
mentioning
confidence: 98%
See 1 more Smart Citation